Social signals and their impact on SEO - Malicoat, Todd (FT Press, 2013)
"Do you want to be a hero with your SEO? Learn how to incorporate social signals into your SEO plans, or you'll miss out on a huge chunk of optimization potential. Here to save the day are SEO experts Todd Malicoat and Philip Petrescu of Caphyon, who will gear you up, help you socialize, and optimize your SEO, all in one lesson. In this workshop you'll learn why you cannot afford to ignore social search, how Google incorporates social signals in its algorithm results, how to understand the most influential weapons in SEO, and how different types of social media affect search."--Resource description page.